Activism Renewed and Beyond: Korean Feminist Documentary Practices in the Twenty-First Century - Jihoon, Kim (Archīum Ateneo, 2024)
This article offers a critical mapping of Korean feminist documentary practices in the twenty- first century, with emphasis on films made since the mid-2010s. The study is grounded in a distinction between the documentaries before and after this period in terms of the feminist politics and the social actors that these films address and engage. In so doing, it argues for three implications of twenty-first century Korean feminist documentary cinema as follows: first, rather than remaining with little remarkable change, the activist tradition of Korean independent documentary has been renewed and revamped in its continual intersections with the shifting social movements for women’s rights; second, since the mid-2010s, the agendas of feminist documentary have been diversified to the extent that they include not simply the lives and voices of disenfranchised women as a key social subject of traditional activist filmmaking before that period, but also the corporeal and affective dimensions of women’s identity, such as abortion and menstruation, and their relation to women’s sociality; and finally, in dialogue with this differentiation of feminist issues, the modes and styles of documentary filmmaking have been so varied that they embrace reenactment, urban ethnography, personal documentary, and the filmmaker’s presence in the text. This is particularly evident in the corpus of Kangyu Garam, a younger-generation woman documentarian who has prolifically demonstrated her authorship with her middle-length and feature-length documentaries devoted to portraying and recording the space and time of various women.